From Recombination Dynamics to Device Performance: Quantifying the Efficiency of Exciton Dissociation, Charge Separation, and Extraction in Bulk Heterojunction Solar Cells with Fluorine‐Substituted Polymer Donors. Issue 4 (28th September 2017) - Gorenflot, Julien; Paulke, Andreas; Piersimoni, Fortunato; Wolf, Jannic; Kan, Zhipeng; Cruciani, Federico; Labban, Abdulrahman El; Neher, Dieter; Beaujuge, Pierre M.; Laquai, Frédéric
Abstract: An original set of experimental and modeling tools is used to quantify the yield of each of the physical processes leading to photocurrent generation in organic bulk heterojunction solar cells, enabling evaluation of materials and processing condition beyond the trivial comparison of device performances. Transient absorption spectroscopy, "the" technique to monitor all intermediate states over the entire relevant timescale, is combined with time‐delayed collection field experiments, transfer matrix simulations, spectral deconvolution, and parametrization of the charge carrier recombination by a two‐pool model, allowing quantification of densities of excitons and charges and extrapolation of their kinetics to device‐relevant conditions. Photon absorption, charge transfer, charge separation, and charge extraction are all quantified for two recently developed wide‐bandgap donor polymers: poly(4, 8‐bis((2‐ethylhexyl)oxy)benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene‐3, 4‐difluorothiophene) (PBDT[2F]T) and its nonfluorinated counterpart poly(4, 8‐bis((2‐ethylhexyl)oxy)benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene‐3, 4‐thiophene) (PBDT[2H]T) combined with PC71 BM in bulk heterojunctions. The product of these yields is shown to agree well with the devices' external quantum efficiency. This methodology elucidates in the specific case studied here the origin of improved photocurrents obtained when using PBDT[2F]T instead of PBDT[2H]T as well as upon using solvent additives. Furthermore, a higher charge transfer (CT)‐state energy is shown to lead to significantly lower energy losses (resulting in higher V OC ) during charge generation compared to P3HT:PCBM. Abstract : The individual efficiencies and losses associated with each step of photocurrent generation in PBDT[2X]T:PC71 BM solar cells are determined using a combination of advanced transient spectroscopic, charge extraction, and steady‐state spectroscopic techniques, aiding the development of a fuller understanding of the complex interplay between chemical structure, thin film processing conditions, and their impact on device performance.